Iman Kabur Generasi Muda: Analisis Personalistik Tentang Krisis Religius Di Era Digital - Neonnub, Patricius (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2025)
This study explores the phenomenon of “blurred faith” among young people in the digital era, where belief often remains declarative but detached from communal participation and relational depth. Drawing on international and Indonesian research, the analysis highlights three expressions of blurred faith: declaration without participation, emotion without doctrinal depth, and moral privatization. Using a personalist framework inspired by Karol Wojtyła, Thomas Aquinas, and Emmanuel Lévinas, the study interprets blurred faith not merely as a decline in religiosity but as a relational crisis—a rupture of the I–Thou encounter with God and others. The paper argues that blurred faith is intensified by digital culture, which favors immediacy and emotional consumption over commitment and solidarity. By situating this phenomenon in the Indonesian context, the study emphasizes the role of local communal values such as gotong royong as a philosophical corrective. The findings point toward the need for personalistic criteria in religious education and pastoral practice to restore faith as a living relational reality.